2022
DOI: 10.3390/ijms23116017
|View full text |Cite
|
Sign up to set email alerts
|

PIF4 Promotes Expression of HSFA2 to Enhance Basal Thermotolerance in Arabidopsis

Abstract: Heat stress (HS) seriously restricts the growth and development of plants. When plants are exposed to extreme high temperature, the heat stress response (HSR) is activated to enable plants to survive. Sessile plants have evolved multiple strategies to sense and cope with HS. Previous studies have established that PHYTOCHROME INTERACTING FACTOR 4 (PIF4) acts as a key component in thermomorphogenesis; however, whether PIF4 regulates plant thermotolerance and the molecular mechanism linking this light transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…To gain mechanistic insights, we first tested whether genes encoding members of HSP families, that play role in heat stress acclimation (Hahn et al, 2011; Li et al, 2023; Yang et al, 2022), are differentially expressed in the knockdown lines. Our analyses showed that the expression of different HSP s is largely compromised in the atipk2β -/- atipk2α kd lines when compared to Col-0 plants (" ref-type="fig">Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To gain mechanistic insights, we first tested whether genes encoding members of HSP families, that play role in heat stress acclimation (Hahn et al, 2011; Li et al, 2023; Yang et al, 2022), are differentially expressed in the knockdown lines. Our analyses showed that the expression of different HSP s is largely compromised in the atipk2β -/- atipk2α kd lines when compared to Col-0 plants (" ref-type="fig">Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The most well-known group of thermoresponsive interacting partners is the phytochrome-interacting factor (PIF) family [ 67 ]. The importance of PIFs for thermomorphogenesis has been observed in Arabidopsis and members of this family have also been identified in wheat, tomatoes, and rice [ 68 , 69 , 70 , 71 ], whereas increased expression levels of PIFs under high temperatures have been confirmed in maize [ 72 ]. The activity of PIF4 can influence the function of the heat-responsive gene EARLY FLOWERING 3 ( ELF3) in Arabidopsis , barley, and wheat [ 73 , 74 , 75 ].…”
Section: Abiotic Stresses and Cropsmentioning
confidence: 99%
“…Several teams pursued this goal as part of the current Special Issue. For example, Yang et al [ 19 ] and Zhang et al [ 20 ] used the Columbia-0 (Col) A. thaliana ecotype to validate the functional roles of PIF4 and AtEAU ( 1 and 2 ) genes, respectively, through transcriptomic tools as boosters and repressors of basal thermotolerance and ABA response. Meanwhile, Kong et al [ 21 ] and Zhang et al [ 22 ], respectively, implemented epigenomics and qRT-PCR in cabbage ( B. oleracea ) and Chinese cabbage ( B. rapa ) to study the DNA methylation footprint during microspore embryogenesis induced by heat shock, and the functional role of BrGOLDEN in carotenoid biosynthesis.…”
Section: Marker-guided Pre-breedingmentioning
confidence: 99%